Evaluation of Diverse Soybean Germplasm for Forage Yield and Quality Attributes. Issue 2 (3rd January 2017) - Rogers, Justin; Florez‐Palacios, Liliana; Chen, Pengyin; Orazaly, Moldir; Jaureguy, Luciano M.; Zeng, Ailan; Wu, Chengjun
Abstract : Information on biomass yield and forage nutritive value of grain‐ and forage‐type soybean [ Glycine max (L.) Merr.] cultivars is of interest to livestock and row‐crop farmers. We studied grain and forage genotypes for biomass, forage nutritive value, and seed yield across two Arkansas locations over 2 yr. Results revealed that stem and total biomass at the R1 (beginning bloom) reproductive growth stage were significantly greater in forage genotypes than in grain genotypes. Forage genotypes had a greater amount of stem biomass (208.7 and 484.0 g m −2 ) at both R1 and R6 stages and leaf biomass (246.2 g m −2 ) at R1 than grain genotypes (140.4, 309.2, and 243.8 g m −2, respectively). At R6, grain genotypes had greater amounts of leaf (388.3 g m −2 ) and pod biomass (350.5 g m −2 ) than forage genotypes (350.4 and 272.5 g m −2, respectively). There were no differences in leaf and total biomass between forage and grain genotypes at R6. Grain genotypes showed significantly greater seed yield than the forage genotypes (2662.3 vs. 1320.2 kg ha −1 ), but no differences in seed protein and oil. Forage genotypes had less crude protein and greater acid detergent fiber than grain genotypes, while their neutral detergent fiber concentrations varied among growth stages. Forage soybeans had lower forage nutritive value than grain soybeans overall. For the southern latitude of Arkansas and southern states, we recommend the late‐maturing forage genotypes 'Tyrone' and 'SG13–53' and grain genotypes 'Arksoy' and 'Centennial' for planting as forage crops. Our results provide valuable information to growers of these distinctly different soybean types.